PENGARUH PEMBERIAN INFORMASI PRABEDAH TERHADAP KECEMASAN PASIEN PRABEDAH TERENCANA DI RUANG BEDAH RSUD R SYAMSUDIN SH KOTA SUKABUMI - Mokhamad Sandi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Background : Giving information preoperative is one of the method For overcome anxiety pre operative . This is very important in help patient overcome his anxiety so that need existence service nursing that quality , this will help reduce the taste Afraid consequence ignorance patient . Objective: study This For know influence giving information pre-operative to anxiety patient pre-operative planned in space Surgery at R. Syamsudin SH Regional General Hospital, Sukabumi City . Research Methods : study This use type quasi- experimental research with one group pretest posttest design . Population in study This is patient pre-operative planned to be treated in the room surgery at R. Syamsudin SH Regional General Hospital, Sukabumi City with amount sample based on Issac and Michael's formula for 53 people. Data collection was carried out with questionnaire , for anxiety data with using the State Anxiety Inventory, which consists of 20 questions . When the normality test was carried out the result is the data is not normality so that in the research This using the Wilcoxon test . Results: level of anxiety patient pre-operative planned before given information pre-operative part big own level worried heavy as many as 28 people (52.8%), the level anxiety patient pre-operative planned after given information pre-operative part big own level worried light as many as 26 patients (49.1%), the Wilcoxon test results obtained a p value of 0.00 where p values <0.05 then There is difference level anxiety patient pre surgery planned before and after given giving information pre surgery . Conclusion : There is influence giving information pre-operative to anxiety patient pre-operative planned in space surgery at R. Syamsudin, SH Regional General Hospital, Sukabumi City